2019
DOI: 10.1080/21691401.2018.1557672
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible disulphide cross-linked sodium alginate derivative nanoparticles for oral colon-targeted drug delivery

Abstract: The application of layer-by-layer (LbL) approach on nanoparticle surface coating improves the colonspecific drug delivery of insoluble drugs. Here, we aimed to formulate a self-assembled cysteaminebased disulphide cross-linked sodium alginate with LbL self-assembly to improve the delivery of paclitaxel (PCX) to colonic cancer cells. Cysteamine was conjugated to the backbone of oxidized SA to form a core of self-assembled disulphide cross-linked nanospheres. P3DL was selected for PCX loading and fabricated LbL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…Lim Vuanghao et al published a report on their use of biocompatible disulphide cross-linked sodium alginate derivative NPs, for targeted oral delivery of PTX to treat colon cancer. They formulated self-assembled cysteamine based disulphide cross-linked sodium alginate NPs, aimed at improving the delivery of PTX to the colon cancer cells [47]. The drug-loaded NPs were reported to have exhibited 77.1% EE and a cumulative drug release of 45.1% in pH 6 medium with GSH.…”
Section: Alginatesmentioning
confidence: 99%
“…Lim Vuanghao et al published a report on their use of biocompatible disulphide cross-linked sodium alginate derivative NPs, for targeted oral delivery of PTX to treat colon cancer. They formulated self-assembled cysteamine based disulphide cross-linked sodium alginate NPs, aimed at improving the delivery of PTX to the colon cancer cells [47]. The drug-loaded NPs were reported to have exhibited 77.1% EE and a cumulative drug release of 45.1% in pH 6 medium with GSH.…”
Section: Alginatesmentioning
confidence: 99%
“…Oliver et al demonstrated that the conjugation of the antioxidant catechin to alg-aldehyde under acidic conditions led to up to 22% functionalization with catechin, involving both nucleophilic addition to the carbonyl group and post-esterification of the carboxylate functionality ( Figure 10) of the functionalized polymers, the chemical modification with thiol-containing units was the key to the sorption properties, which was probably due to their role as cross-linkers between the polymeric chains [88]. 3-11% NaBH4 Drug delivery [86] Imine formation on oxidized alg derivatives was also applied to engineer alg/chitosan or alg/hyaluronic acid hydrogels for protein delivery [90] and cardiac tissue engineering [91].…”
Section: Chemical Modification Of Oxidized Alginatesmentioning
confidence: 99%
“…Oliver et al demonstrated that the conjugation of the antioxidant catechin to alg-aldehyde under acidic conditions led to up to 22% functionalization with catechin, involving both nucleophilic addition to the carbonyl group and post-esterification of the carboxylate functionality ( Figure 10) [92]. NaBH 4 Drug delivery [86] Numerous alg derivatives resulting from reductive amination were developed for drug delivery purposes. The conjugation of amino-thiophenol [85], cysteine [82], or cysteamine [86] to oxidized alg led to self-assembled nanospheres, cross-linked through disulfide bridge formation, which are sensitive to redox potential variations for controlled release of the entrapped drugs.…”
Section: Chemical Modification Of Oxidized Alginatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro drug release studies were conducted at 37 ± 0.1 • C in a shaker incubator at 50 rpm. Hydrochloric acid solution (pH 1.0, stomach), phosphate buffer solution (pH 7.4, small intestine), and phosphate buffer solution (pH 6.0) with and without GSH (colon) were used to simulate the pH and reducing environment of the GIT [20,44].…”
Section: Preparation Characterisation and In Vitro Drug Release Studmentioning
confidence: 99%